A Substantial Role of Agro-Textiles in Agricultural Applications - Sharma, Neha; Allardyce, Ben; Rajkhowa, Rangam; Adholeya, Alok; Agrawal, Ruchi (Frontiers in Plant Science, 2022)
Agro-textiles have been used in the agriculture sector for thousands of years and are an attractive tool for the protection of crops during their entire lifecycle. Currently, the agro-textile market is dominated by polyolefins or petrochemical-based agro-textiles. However, climate change and an increase in greenhouse gas emissions have raised concern about the future oil-based economy, and petroleum-based agro-textiles have become expensive and less desirable in the modern world. Other products include agro-textiles based on natural fibers which degrade so fast in the environment that their recovery from the field becomes difficult and unattractive even by efficient recycling or combustion, and their lifetime is usually limited to 1 or a maximum of 2 years. Hence, the development of bio-based agro-textiles with a reduced impact on the environment and with extended durability is foreseen to initiate the growth in the bio-based economy. The world is gradually preparing the shift toward a bio-based economy, and research for sustainable bio-based alternatives has already been initiated. This review provides insight into the various agro-textiles used currently in agriculture and the research going on in the area of agro-textiles to offer alternative solutions to the current agro-textile market.